Addition of mycotoxin binders to animal feeds to reduce aflatoxin concentration in cow milk: adaptation to smallholder dairy systems in low- and middle-income countries - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
A study was conducted to investigate the availability and use of mycotoxin binders in selected urban and peri-urban areas of Kenya and results published. The study provided key data on the availability and local use of mycotoxin binders, which were previously lacking.